If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3f = 20 + -1f Solving 3f = 20 + -1f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add 'f' to each side of the equation. 3f + f = 20 + -1f + f Combine like terms: 3f + f = 4f 4f = 20 + -1f + f Combine like terms: -1f + f = 0 4f = 20 + 0 4f = 20 Divide each side by '4'. f = 5 Simplifying f = 5
| 2.49+1.24x=11.17 | | 80+4x=100 | | 5(2x-3)=2(3x+7) | | 0.45(d-1.2)+0.67=5.53 | | 0.22n+n=3.55 | | 10=0.66m-1.5m | | a^2+a*b+8*a+8*b= | | .83(12-5b)=35 | | 5ab+10a= | | 2x+1=0 | | 5+3=14 | | X^3-8x^2-16x=0 | | X^3-8x^2+16x=0 | | 148=4x+40 | | X^3-x(8x-16)=0 | | 3(-21+7)=2(-21) | | X^3+18x^2+16x=0 | | x^2+10x+25=49 | | 6(x+2)=48 | | x^2+10x+25=40 | | 128-14x=16 | | -10y=-120 | | -8f=63-f | | 4-(-1)= | | x^3+8x^2+4x+48=0 | | 3n+2=5n+3 | | 3n+2=5n+2 | | 3=0.25(m-4)+0.25m | | 36+8x-16=48-4x+50 | | 0.5x^2+x-4=0 | | x^4-4x^4y^4+y^4=x^4+4x^4y^4+y^4 | | (2c-9)(c+8)=0 |